Co(Salox)‐Catalyzed Enantioselective Reduction of α, β‐Unsaturated Esters. Issue 17 (28th February 2023) - Pugliese, Giacomo; Vaghi, Francesco; Lonardi, Giovanni; Licini, Giulia; Orlandi, Manuel
Abstract: Co‐Salox complexes are suitable catalysts for the reduction of prochiral α, β‐unsaturated esters. These ligands can be prepared in a single step from available and inexpensive materials, thus representing an easily accessible alternative to previously reported Co‐catalysts. NaBH4 is employed as reducing agent in the presence of EtOH as proton source, leading to the stereoselective formation of chiral esters, amides, and nitriles in up to 99 % yield and 96.5 : 3.5 er . The concentration of the reductant counter cation (Na + ) and the solvent polarity have been shown to correlate with reactivity and enantioselectivity, suggesting that a relatively complex mechanistic manifold is in place. Abstract : Easily accessible Salox ligands in combination with cobalt were found to be competent catalysts for the asymmetric conjugate reduction of α, β‐unsaturated esters, amides, and nitriles with NaBH4 To give enantioselectivity up to 96.5 : 3.5 er and quantitative yields. Preliminary experiments highlight a relatively complex reaction mechanism.